Seasonal impact in admissions and burn profiles in a desert burn unit - Syed F. Saquib; Joseph T. Carroll; Paul Chestovich (Elsevier, 2021)
In much of the world, pattern of burn injuries can vary depending on the season. This study examines the seasonal impact of admissions, acuity, mortality, and resource utilization at an accredited burn center located in a desert climate. It is a retrospective analysis of patients admitted from March 1, 2014 to February 28, 2019 for acute burns. Patients were categorized into four groups according to each season based on their date of admission: Spring (March, April, May), Summer (June, July, August), Fall (September, October, November), and Winter (December, January, February).A total of 1519 patients were included. 1016 were male (66.9%) with an average age 39.6 years. Most admissions came during the Summer (35%), followed by Winter (23%), Spring (21%) and Fall (21%). Most common mechanisms are flame/flash (677, 44.6%), scald (414, 27.3%) and pavement (194, 12.8%). 169 (87.1%) of 194 pavement burn admissions occurred during the Summer. Average hospital LOS was 18.7 days, longest for pavement at 25.8 days, flash/flame 21.9 days and electrical 11.8 days. Log-rank test of LOS showed longer LOS for pavement burns compared to all other etiologies combined. Average daily census was highest in Summer (14.1), followed by Winter (9.8), Spring (8.7) and Fall (7.1).Summer was the peak season for burn admissions and average daily census in large part from pavement burns. As these burns have a longer LOS, it leads to increase in resource utilization compared to the other mechanisms. Volume of non-pavement burns appear steady throughout the year.